160 Normal Pressure Hydrocephalus Medicare Expenditures (2006-2010). Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Vivas-Buitrago, Tito G M; Rigamonti, Alessandra; Pinilla-Monsalve, Gabriel David; Carson, Kathryn A; Sharkey, Phoebe; Robison, Jamie; Jusué-Torres, Ignacio; Clemens, Gwendolyn; Sanyal, Abanti; Hoffberger, Jamie; Sankey, Eric W; Lu, Jennifer; et al.
Abstract: INTRODUCTION: A previous study of the Medicare database has shown that Normal Pressure Hydrocephalus (NPH) is an underdiagnosed condition affecting the elderly population and that the costs associated with its surgical management are less than those associated with conservative management. Our aim is to determine if the rate of diagnosis of NPH has improved over the last decade and if surgical treatment costs have remained lower than those associated with conservative therapy. METHODS: Retrospective study based on data from a nationally representative random sample of 2378 637 Medicare beneficiaries (2006-2010). Cohort population was defined as patients with NPH (ICD-9-CM 331.3, 331.4, and 331.5). Two measures of shunt surgery (presence of shunting procedure and number of days after the first shunt procedure was performed) were used and shunt revision, replacement, and removal were analyzed as independent variables. Five primary outcome measures for NPH healthcare expenditures were assessed by using linear and logistic models. RESULTS: A total of 2321 patients with NPH (0.2% prevalence) were included, with 580 (24.99%) receiving a first shunt procedure. The adjusted effect of the procedure is that total 5-yr expenditures are 11 676 more per patient ( P < .001) than expenditures associated with nonsurgical management. Shunt revision (22 715, P < .01) and/or replacement (46 607, P < .001), add significantly to 5-yr expenditures. CONCLUSION: There was a 1.66-fold increase in the rate of diagnosis of NPH, from 0.12% in 1999 to 0.2% in 2008. The total costs per surgical patient rose by approximately 145 to 160% comparing 2001 and 2010. This increase was mainly due to hospital (by 167-168%) and home health costs (by 118-148%).